Identification of suspected fatal adverse drug reactions by paediatricians: a UK surveillance study. Issue 7 (22nd June 2007) - Cheng, K; Masters, S; Stephenson, T; Cooke, R; Ferner, R; Ashworth, M; Nunn, A J
Abstract : This British Paediatric Surveillance Unit (BPSU) study on adverse drug reactions (ADRs) in children was initiated because of concern that there might be under-reporting of serious ADRs in children using the yellow card scheme. We aimed to quantify the frequency of fatal ADRs in children under the age of 16 years in the United Kingdom and Ireland. The surveillance period ran for 13 months from June 2002 to June 2003, inclusive, and approximately 2000 cards were sent out monthly by the BPSU to consultant paediatricians in the United Kingdom and Ireland. In total, seven reports meeting the study criteria were received. Causality assessment was undertaken by an independent expert panel using formal, published criteria. In two of the deaths, the panel did not reach consensus and causality assessments varied from possible to certain. Five of the seven deaths were unanimously thought to be unlikely to be causally related to the index drug. Overall this study does not provide evidence of a major public-health concern relating to fatal ADRs in children. However, the limitations of the study mean that some fatal ADRs may have been unrecognised or unreported.